(untitled) (Journal of the College of Basic Education, 2022)
The teaching of history faces many problems that its nature and organization have contributed to highlighting.Because it is characterized by a large degree of expansion, which made many teachers resort to using itTeaching methods and methods depend on memorizing historical facts and information without understanding or understanding studentsRealizing the interdependence between them, which leads to poor achievement among students. Therefore, the current research aimed to identify the methods and methods commonly used in teaching a subjecthistory in middle school; From the point of view of its teachers, teachers and supervisors.